2013
DOI: 10.1007/s00068-013-0338-7
|View full text |Cite
|
Sign up to set email alerts
|

Triplane fractures: do we need cross-sectional imaging?

Abstract: The additional information of cross-sectional imaging seems helpful for any physician in finding the right classification of a pediatric ankle fracture. However, the additive information appears especially viable for experienced surgeons to suggest the appropriate treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 34 publications
0
9
0
1
Order By: Relevance
“…The commonly accepted treatment goal in transitional fractures is the anatomic reduction of the articular surface [10-17, 20, 33, 34], as longitudinal growth at the time of physeal plate maturation is complete, the remodeling potential of these fractures is limited [17,33,34]. We suggest CT scan with multiplanar reconstruction for displaced transitional fractures for a closer understanding of the fractures and to allow for better treatment planning [34,36,37]. Non-operative treatment (immobilization in a forearm cast for at least 4 to 6 weeks) of transitional fractures of the distal radius is recommended only for non-or minimal (less than 2 mm) displaced fractures or if anatomical reduction and maintenance of reduction could be achieved by closed manipulation.…”
Section: Discussionmentioning
confidence: 99%
“…The commonly accepted treatment goal in transitional fractures is the anatomic reduction of the articular surface [10-17, 20, 33, 34], as longitudinal growth at the time of physeal plate maturation is complete, the remodeling potential of these fractures is limited [17,33,34]. We suggest CT scan with multiplanar reconstruction for displaced transitional fractures for a closer understanding of the fractures and to allow for better treatment planning [34,36,37]. Non-operative treatment (immobilization in a forearm cast for at least 4 to 6 weeks) of transitional fractures of the distal radius is recommended only for non-or minimal (less than 2 mm) displaced fractures or if anatomical reduction and maintenance of reduction could be achieved by closed manipulation.…”
Section: Discussionmentioning
confidence: 99%
“…CT scan is most commonly indicated for transitional fractures to study the configuration of fracture, the number of fracture fragments and displacement and also to plan the fixation. Though some authors have concluded that CT scan would not significantly change the way these fractures are managed, there is enough evidence in the literature to support the use of routine CT scan to analyse and treat these fractures [14][15][16][17]. Many a time, there would be a change of treatment plan after viewing CT imaging because of the significant intraarticular displacement that is difficult to appreciate on plain radiographs [16].…”
Section: Imagingmentioning
confidence: 99%
“…Though there is controversy on the routine need of CT scans for evaluation of triplane injuries [14][15][16]47], we feel that CT scan is mandatory in these fractures both for quantifying the displacement as well as planning the screws which primarily depends on the number and location of fragments (Fig. 9).…”
Section: Triplane Fracturesmentioning
confidence: 99%
“…Eine genaue Differenzierung zwischen Twoplane-, Triplane-I-und -II-Frakturen ist oft nur anhand einer Schnittbildgebung möglich [10,11]. Sie wird v. a. zur Beurteilung des dorsalen Frakturabschnitts und bei vermeintlich undislozierten Übergangsfrakturen empfohlen.…”
Section: Diagnostikunclassified